Biochemistry navigation application with 5-ALA for surgical treatment of cerebral tumors with various histological types - G. I. Kovalev; V. E. Kocharyan; G. G. Muzlaev (Инновационная медицина Кубани)
Application of 5-aminolevulinic acid (5-ALA) in surgery for gliomas with high grade of malignancy according to clinic guidelines for intraoperative fluorescence diagnostics usage has become a standard modality. However possibilities of intraoperative fluorescent diagnostics with 5-ALA in surgery for other cerebral tumors are not studied well enough.Objective. We analyzed usage results of biochemical navigation with 5-ALA in cases with cerebral tumors of various histological types.Material and Methods. In the study we included 89 patients with various cerebral tumors: gliomas Grade I-IV WHO, metastatic spread and a single case with anaplastic meningioma of different localization. In our study we applied the agent 5-ALA Alasens FGUP «SSC NIOPIK». All patients underwent tumor removal with microsurgical technique, intraoperative optics and metabolic navigation with 5-ALA. Intraoperatively we applied following tools: a microscope OPMI Carl Zeiss Pentero with fluorescent module. We performed expert quality evaluation of fluorescent grade according to 4-rating scale adopted in N.N. Burdenko Scientific Research Institution.Results. We received rather high frequency of fluorescence in all studies. High efficiency of this technique in surgery of gliomas with high malignancy degree was confirmed. High sensitivity during removal of gliomas with low malignancy degree and metastasises was reached excluding the factors which are not connected with biochemical processes in a tumor. The single case of 5-ALA application with anaplastic meningioma confirms efficiency of this method to identify tumorous invasion in visually not changed dura mater.Conclusion. Metabolic navigation at the majority of histologic types of tumors is the highly effective means of intraoperative timorous demarcation which does not depend on changes of intracranial volume relationships, allowing to gain rather quickly an impression on the metabolic status of a tumor and to reach the maximum radicalism.